Sunnah-Centered Religious Culture as an Innovative Approach to Islamic Character Development - Sandia, Hani; Kosasih, Aceng; Fakhruddin, Agus (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2025)
This study aims to systematically and contextually describe the planning, processes, and outcomes of implementing a Sunnah-based religious culture at Bandung Islamic School as a strategy for shaping student character in the modern era. The research employed a qualitative approach using interviews, observations, and document analysis. Data were analyzed through the stages of reduction, display, and conclusion drawing. The planning of the religious culture was carried out through the integration of the school’s vision and mission into the curriculum, the development of structured programs, the strengthening of school regulations, and the establishment of a monitoring and evaluation system. The implementation was comprehensive, encompassing an integrated curriculum; worship habituation; tahfidz classes; hadith memorization; daily Sunnah-based etiquette programs; Sunnah sports; Islamic female student development (keputrian syar’i); and Sharia-compliant counseling, all reinforced by teacher role modeling and a mutaba’ah monitoring system. This implementation resulted in significant changes in students’ behavior and character, as well as the creation of a religious school climate. The findings affirm that students internalize a Sunnah-based religious culture as a religious habitus through mechanisms of habituation, role modeling, and participatory supervision. Theoretically, this research enriches the concept of religious value habituation in modern Islamic education by integrating the perspectives of comprehensive tarbiyah, ta’dib, and ta’wīd. This study presents a strategic model for developing Islamic education in the digital era, which other educational institutions can adapt to make the Sunnah a living and applicable source of values across all dimensions of school life.